Analysis of the Application of e-Book Learning Media in English Subjects at Elementary School 1 Boja - Sri Wahyuni; Muhammad Arief Budiman; Ratna Wahyu Pusari; Muhammad Aniq Khoirul Basyar (Universitas Muria Kudus, 2025)
Various learning media are available in the world of education which can be an option for educators to choose learning media that suits the conditions of their respective classes. This research aims to analyze the use of e-book learning media in English classes at elementary School 1 Boja (SDN 1 Boja). This research is descriptive qualitative research. Data collection methods use interviews, questionnaires, and observation. The research results showed that the use of e-book learning media has various positive impacts, including: increasing students' learning motivation, improving students' interest in learning, and increasing students' activeness during the teaching and learning process. The conclusion obtained is that e-book learning media has a positive impact on the English language learning process in elementary schools. It is recommended that e-book learning media also be applied to other subjects.